2011
DOI: 10.3109/01480545.2011.564177
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant and antiproliferative effects of the 1,3,4-thiadiazole–based Schiff base and its metal complexes

Abstract: Adverse biological activities of Schiff base (SB) derivatives are well known. In this study, the ligand and its metal complexes have been synthesized and characterized by IR, (1)H-NMR spectra, elemental analyses, magnetic susceptibility, UV-Vis spectra, and thermogravimetry/differential thermal analysis. From the elemental analyses data, the complexes were proposed to have the general formula [Mn(L)(2)(H(2)O)(2)], [Co(L)(2)(H(2)O)(2)], and [Ni(2)(L)(H(2)O)(4)(Cl)(3)]. From the magnetic moment and UV-Vis spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Regarding antifungal activity, the compound showed a better anti- Candida effect than fluconazole, used as the reference drug. Previous studies showed that SBs have the ability to modulate oxidative stress [17, 39]. This ability can be exploited in order to use them as antibacterial drugs and/or as potential oxidative stress modulators in medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding antifungal activity, the compound showed a better anti- Candida effect than fluconazole, used as the reference drug. Previous studies showed that SBs have the ability to modulate oxidative stress [17, 39]. This ability can be exploited in order to use them as antibacterial drugs and/or as potential oxidative stress modulators in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed the ability of SBs to act as antiproliferative and antitumoral agents [1416]. The azomethine pharmacophore is used in developing new bioactive molecules [17]. The discovery of selective cytotoxic drugs influenced oncological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…reported that 1,3,4-thiadiazole-based Schiff base and its metal complexes did not change serum vitamins A, E, and C levels. However, they reported that vitamin levels were lower in treatment groups, compared to the control group in the liver tissues (22). In another study by Karatepe and Karatas (13) found that serum vitamins A, E concentrations were statistically changed but serum level of vitamin C was not changed.…”
Section: Lipophilic Vitaminsmentioning
confidence: 92%
“…The compounds containing 1,3,4‐thiadiazole moiety show interesting pharmacological activities as well as properties useful from the technological and agricultural point of view . Their antibacterial, antiviral, anticancer, antiparasitic, anti‐inflammatory, anticholinergic and antihistamine activities have been widely studied. Some compounds belonging to this class are potent radioprotective agents .…”
Section: Introductionmentioning
confidence: 99%